Marine recreation with a purpose: an emerging form of marine citizen science in the Ocean Decade - Fantuzzi, Laura; Ford, Alex T.; de Laszlo, William; Lundgren, Andrew; Couceiro, Fay (Frontiers in Sustainable Tourism, 2023)
Amidst the growth of the marine technology and recreation sectors and heightened public environmental awareness, the opportunity for marine citizen science is extending to marine recreationalists. An unnoticed yet growing demand for purpose among marine recreationalists has translated into citizens recruiting scientists to integrate environmental data collection into recreational activities or events, named here “marine recreation with a purpose.” As an example, GB Row Challenge is an annual ocean rowing competition circumnavigating Great Britain which recently integrated environmental monitoring as an inherent component of the event with the help of partner scientists and engineers. This bottom-up, integrated form of marine citizen science that is rooted in recreation, adventure or sports, has unique contributions to United Nations' Ocean Decade goals, such as encouraging ocean stewardship and normalizing citizen science and ocean literacy to audiences not usually exposed to this content. The public nature of these projects may also help overcome common barriers of citizen science with funding and technical support by private sources via sponsorships. To build the experiential, financial and technical capacities needed to enable marine recreation with a purpose at all scales, coordination between all forms of marine recreation-based citizen science is required. This could be realized through forming a dedicated coalition in existing citizen science associations and platforms. Marine recreation with a purpose is a growing trend of citizen science in the marine recreation sector and global coordination will amplify its impact as an essential contribution to the Ocean Decade.